Vulnerability and young people care and social control in policy and practice - Brown, Kate 1980- (Policy Press, 2015)
This book draws on in-depth research with marginalised young people and the professionals who support them to explore the implications of a 'vulnerability zeitgeist', asking how far the rise of vulnerability in welfare and criminal justice processes serves the interests of those who are most disadvantaged
Title from publisher's bibliographic system (viewed on 08 Mar 2022)
Keywords: Young adults / Psychology; Young adults / Social conditions; Conflict of generations